Herman Melville's Moby-Dick - Bloom, Harold (New York : Chelsea House Publishers, 1986)
A collection of eight critical essays on Melville's novel "Moby Dick" arranged in chronological order of publication.
Call me Ishmael / Charles Olson -- In nomine diaboli / Henry A. Murray -- Herman Melville / David Simpson -- The career of Ishmael's self-transcendence / Rowland A. Sherrill -- Moby-Dick, an American lyrical novel / Bert Bender -- Speech in Moby-Dick / Louise K. Barnett -- The metaphysics of beauty and terror in Moby-Dick / Frank G. Novak, Jr. -- Ahab's name / P. Adams Sitney.
Includes bibliographical references (p. 151-152) and index.
Young Adult
Keywords: Melville, Herman, -- 1819-1891.; American literature -- History and critcism